The Degree of Success on Ex-psychotic Homeless Rehabilitation - Chulaifah Chulaifah; Sri Prastyowati (Jurnal Penelitian Kesejahteraan Sosial, 2016)
This research done to know the degree of success on homeless expsychotic rehabilitation seen from misconduct behavior aspect. Research location was at Pojoreken Homeless Institution, Medan Municipality, North Sumatera Province.Data gathered through documentary analysis of 15 files of moderate ex-homeless psychotic at the institution. Data are analysed through qualitatif-descriptive technique, on the degree of success of guidance, self and social realization, social integration, work skill and vocation seen from misconduct behavior during rehabilitation. The research found that the ability of self and social realization, social integration after rehabilitation was not significant, execpt in work and vocational skills. The degree of fequency of misconduct behaviors do not immidiately change the ability of self and social realizations, social integration, except in work and vocational skills. Those because there was psychological and social problems, indicated in continously labil emotion that manifested through â€œsmilingâ€, talk with him/herself, angry without any reason, retreat, easy-go, egoism, rage violently, confused, rejection, reluctant, strained, self hurting, lazy, steal, seek for rejected things, litering, silence, do not want bathing, talk all times, hurt others, and go anywhere. The research recommends that the guidance should be held continously, aspecially after rehabilitation and back to the community. Guidance should be given by those who understand on characteristic of homeless psichotic. It needs socialization among communities on homeless psichotic characteristic and services they need.